A framework for the interpretation of temperature effects on dormancy and germination in seed populations showing dormancy - Batlla, Diego (2015)
Temperature is a key factor affecting both dormancy and germination. In non-dormant seeds, when temperature is within the thermal range permissive for germination, it just regulates germination velocity, while in seeds presenting dormancy it can also be affecting dormancy level, dormancy termination and the expression of dormancy itself. This dual effect of temperature on dormancy and germination often leads to misinterpretation of obtained germination results and confounds the analysis of temperature effects in seed populations presenting some degree of dormancy. In the present paper we discuss the effect of temperature in the regulation of dormancy level and its implications in dormancy expression, as an attempt to construct a conceptual framework that allows distinguishing between the effects of temperature on dormancy and germination. Finally, we present examples of how a better understanding of these effects could help us to interpret the mixed effects of temperature on both processes during incubation of seeds presenting dormancy.